Determinants of gestational weight gain during pregnancy in a multiethnic UK-based population: Findings from the Born in Bradford cohort study - Petra A. T. Araújo; Maria A. Quigley; Gillian Santorelli; Victoria Coathup (PLoS ONE, 2025)
Introduction Unhealthy maternal weight gain during pregnancy is associated with deleterious outcomes to mothers and their offspring. Current literature on the determinants of gestational weight gain yields inconsistent results, with limited research conducted in the United Kingdom. This study investigates potential determinants of unhealthy gestational weight gain in a multiethnic cohort within Bradford, United Kingdom. Methods The study analysed 7,769 singleton pregnancies from the Born in Bradford Cohort. Women were enrolled at ~26 weeks’ gestation. Weight at first antenatal appointment, recruitment and/or third trimester were used to calculate weekly average weight gain. This was categorized as ‘less than recommended’, ‘recommended’ or ‘more than recommended’ based on the Institute of Medicine (IOM) criteria. Associations between potential determinants and gestational weight gain were assessed using multinomial logistic regression with recommended gestational weight gain as the reference. Results Overall, 22.4% of women gained weight within the recommended range; 20.3% gained less than recommended, and 57.3% gained more than recommended. Key risk factors for gaining less weight than recommended were unhealthy baseline BMI (aOR=1.78 for underweight, aOR=1.3 for obese), higher parity (e.g. aOR=1.46 for 3 + children) and lower socioeconomic status (aOR=1.4). The strongest risk factors for gaining more weight than recommended were high baseline BMI (e.g. aOR=5.86 for obese) and higher psychiatric morbidity score (aOR=1.22); being underweight (aOR=0.58) and higher parity (e.g. aOR=0.70 for 3 + children) were associated with a lower risk of gaining more weight than recommended. The effect of mental health seemed to be particularly important among women of Pakistani background, while parity seemed to play a major role among White British women. Conclusion Baseline BMI, age, socioeconomic position, parity and mental health are associated with unhealthy weight gain during pregnancy in a multiethnic UK population. These findings can help identify at-risk women and inform targeted preventative strategies.